A distributed virtual reality framework for Korea-Japan high-speed network test bed. (8th June 2009) - Nishino, Hiroaki; Yamabiraki, Shinji; Kagawa, Tsuneo; Utsumiya, Kouichi; Kwon, Yong-Moo; Okada, Yoshihiro
A framework to practically constitute a Distributed Virtual Reality (DVR) system on a heterogeneous high-speed network environment is shown. The proposed approach essentially integrates a 'haptic' channel into traditional vision and acoustic modalities. The haptic technology empowers the reality of the DVR system by allowing users to touch virtual objects. The human touch sensation, however, is very sensitive to delays and jitters; therefore, we propose a hybrid DVR architecture to realise both data consistency by client-server and scalability by peer-to-peer models on a long-haul network. Some experiments using a Korea-Japan high-speed research network are described to validate the proposed method.